Gestão e gerenciamento de resíduos eletroeletrônicos da Polícia Militar de Sergipe - Silva, Keeze Montalvão Fonseca da (2020)
In modern society, the production and accumulation of electrical and electronic equipment has been one of the challenges faced with regard to socio-environmental issues, especially in the management of solid waste, as the amount of electronic waste has been growing proportionally to the technological development in the various segments of society. With the Sergipe Military Police (PMSE), it is no different, given the need / desire to replace worn out or “outdated” electronic devices with new ones that are used both in the administrative part and in the exercise of ostensive policing. Thus, this research aims to analyze the management and management of Waste Electrical and Electronic Equipment (WEEE) discarded by the Sergipe corporation. To carry out this research, the “Case Study” was anchored with a methodological approach supported by the hypothetical-deductive method based on a quali quantitative study, with predominance in the qualitative approach. Regarding the methodological procedures, the following steps were performed: bibliographic and documentary survey; field research, with systematic observation and photographic records, semi-structured interview; organization, tabulation and analysis of information. The PMSE has police units in all municipalities in the state of Sergipe, which fulfills its constitutional mission through 11 (eleven) battalions, with a semi-structured interview being conducted with the 11 (eleven) military police representatives of these battalions who work in the process of management and management of WEEE from these police Units. The results obtained showed that the PMSE performs a WEEE management and management process, without much organization and control in their storage. WEEE is divided by the Military Police (PM) into two groups: the paid and the non-paid. Patrimonial waste is returned to the State Secretariat for Budget Planning and Management (SEPLAG), which after the internal procedure holds an auction open to the public. After the auction, the destination and the final disposition that is given to these residues are not known, since it is the responsibility of the bidders, according to decree nº 9.373 / 2018, Art. 9, since there is no inspection or monitoring about this destination by the secretariat. Unapproved residues remain at battalion headquarters until a hierarchical superior determines what their destination will be, without any control and standardization over what can be done with such residues. In this sense, the relevance of institutionally standardizing the procedures to be adopted in dealing with WEEE within the scope of the PMSE is well known. The aforementioned standardization can be carried out through the creation of an internal policy, and a management and management plan for heritage and non heritage waste, giving publicity and standardization to the procedures that must be adopted by the battalions, as recommended by Art. 9, of Law No. 12,305 / 2010 - National Policy on Solid Waste (PNRS).